Amyloid fibril proteins and amyloidosis: chemical identification and clinical classification International Society of Amyloidosis 2016 Nomenclature Guidelines. (1st October 2016) - Sipe, Jean D.; Benson, Merrill D.; Buxbaum, Joel N.; Ikeda, Shu-ichi; Merlini, Giampaolo; Saraiva, Maria J. M.; Westermark, Per
Abstract: The Nomenclature Committee of the International Society of Amyloidosis (ISA) met during the XVth Symposium of the Society, 3 July–7 July 2016, Uppsala, Sweden, to assess and formulate recommendations for nomenclature for amyloid fibril proteins and the clinical classification of the amyloidoses. An amyloid fibril must exhibit affinity for Congo red and with green, yellow or orange birefringence when the Congo red-stained deposits are viewed with polarized light. While congophilia and birefringence remain the gold standard for demonstration of amyloid deposits, new staining and imaging techniques are proving useful. To be included in the nomenclature list, in addition to congophilia and birefringence, the chemical identity of the protein must be unambiguously characterized by protein sequence analysis when possible. In general, it is insufficient to identify a mutation in the gene of a candidate amyloid protein without confirming the variant changes in the amyloid fibril protein. Each distinct form of amyloidosis is uniquely characterized by the chemical identity of the amyloid fibril protein that deposits in the extracellular spaces of tissues and organs and gives rise to the disease syndrome. The fibril proteins are designated as protein A followed by a suffix that is an abbreviation of the parent or precursor protein name. To date, there are 36 known extracellular fibril proteins in humans, 2 of which are iatrogenic in nature and 9 of which have also been identified in animals. Two newly recognized fibril proteins, AApoCII derived from apolipoprotein CII and AApoCIII derived from apolipoprotein CIII, have been added. AApoCII amyloidosis and AApoCIII amyloidosis are hereditary systemic amyloidoses. Intracellular protein inclusions displaying some of the properties of amyloid, "intracellular amyloid" have been reported. Two proteins which were previously characterized as intracellular inclusions, tau and α-synuclein, are now recognized to form extracellular deposits upon cell death and thus have been included in Table 1 as ATau and AαSyn.